1996
DOI: 10.1088/0264-9381/13/11/018
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional integrable vacuum cosmology with two curvatures

Abstract: The vacuum cosmological model on the manifold describing the evolution of n Einstein spaces of non-zero curvatures is considered. For n = 2 the Einstein equations are reduced to the Abel (ordinary differential) equation and solved, when . The Kasner-like behaviour of the solutions near the singularity is considered ( is synchronous time). The exceptional (`Milne-type') solutions are obtained for arbitrary n. For n = 2 these solutions are attractors for other ones, when . For and certain two-parametric fami… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 27 publications
3
28
0
Order By: Relevance
“…We have shown that this result is compatible with the exact 1 + 3 + 6 solution from Ref. [54]. (Recall that only three exact solutions are known for a vacuum cosmological model with a product of two Einstein spaces, see Ref.…”
Section: óò ðù× óò×supporting
confidence: 84%
See 1 more Smart Citation
“…We have shown that this result is compatible with the exact 1 + 3 + 6 solution from Ref. [54]. (Recall that only three exact solutions are known for a vacuum cosmological model with a product of two Einstein spaces, see Ref.…”
Section: óò ðù× óò×supporting
confidence: 84%
“…(Recall that only three exact solutions are known for a vacuum cosmological model with a product of two Einstein spaces, see Ref. [54]. ) We also presented another example where two factor spaces are Ricci-flat and for a two-component example (dust + 5-brane) we obtained a small enough variation of G.…”
Section: óò ðù× óò×mentioning
confidence: 96%
“…For the two component perfect-fluid there were solutions with two curvatures, i.e. n = 2, (3,6), (5,5) [106] and corresponding non-singular solutions from [141]. Among the solutions [106] there exists a special class of Milne-type solutions.…”
Section: Multidimensional Modelsmentioning
confidence: 99%
“…n = 2, (3,6), (5,5) [106] and corresponding non-singular solutions from [141]. Among the solutions [106] there exists a special class of Milne-type solutions. Recently some interesting extensions of 2-component solutions were obtained in [107].…”
Section: Multidimensional Modelsmentioning
confidence: 99%
“…Nonlinear ordinary differential equations play a significant role in many physical and technical applications [7,8,16,17,21,27,29,30]. Most of these equations have no analytical solution and numerical techniques may be used to obtain approximate ones.…”
Section: Introductionmentioning
confidence: 99%